Bioactive Tape With BMP-2 Binding Peptides Captures Endogenous Growth Factors and Accelerates Healing After Anterior Cruciate Ligament Reconstruction. Issue 12 (October 2018) - Crispim, João F.; Fu, Sai C.; Lee, Yuk W.; Fernandes, Hugo A.M.; Jonkheijm, Pascal; Yung, Patrick S.H.; Saris, Daniël B.F.
Background: The anterior cruciate ligament (ACL) has poor regenerative capacity, and an injury leads to loss of function, limiting quality of life and increasing the incidence of osteoarthritis. Surgical interventions can stabilize the joint and improve functional recovery. The delivery of growth factors (GFs) enhances the healing process; however, this is complex in its regulation, is high in costs, has side effects, and can only be accomplished with supraphysiological concentrations and thus is currently not clinically feasible. However, the immobilization of a patient's endogenous GFs in biomaterials can overcome these problems. Purpose: To develop a method to capture endogenous bone morphogenetic protein–2 (BMP-2) and ultimately show enhanced ACL healing in vivo using this novel methodology. Study Design: Controlled laboratory study. Methods: BMP-2 binding peptides were synthetized, purified, and immobilized on polycaprolactone (PCL) films. The affinity between the peptide and human BMP-2 (hBMP-2) was confirmed with immunofluorescence and enzyme-linked immunosorbent assay. The C2C12 Luc reporter cell line was used to confirm the bioactivity of immobilized BMP-2. For in vivo experiments, the same functionalization technology was applied to the commercially available Polytape, and the functionalized tape was sutured together with the graft used for ACL reconstruction in rats. Each animal underwent reconstruction with either native Polytape (n = 3) or Polytape with BMP-2 binding peptides (n = 3). At 2 and 6 weeks after surgery, the graft was assessed by histology and micro–computed tomography. Results: The covalent immobilization of the peptide in PCL was successful, allowing the peptide to capture hBMP-2, which remained bioactive and led to the osteogenic differentiation of C2C12. In vivo experiments confirmed the potential of the Polytape functionalized with the BMP-2 binding peptide to capture endogenous BMP-2, leading to enhanced bone formation inside the femoral and tibial tunnels and ultimately improving the graft's quality. Conclusion: The incorporation of BMP-2 binding peptides into materials used for ACL reconstruction can capture endogenous hBMP-2, which enhances the healing process inside the bone tunnels. Clinical Relevance: These results demonstrate the potential of using synthetic peptides to endow biomaterials with novel biological functions, namely to capture and immobilize endogenous GFs.